Memories in the elderly living with the immunodeficiency virus - Luana de Fátima Garcia de Freitas; Daniela Garcia Damaceno; Miriam Fernanda Sanches Alarcon; Patrícia Regina de Souza Sales; Maria José Sanches Marin (Universidade Federal de Santa Maria, 2020)
Objective: to understand the experiences of the elderly with Human Immunodeficiency Virus on the main factors that mark their memories. Method: this is a qualitative study with a narrative method, conducted from April to May 2018 in a medium-size city in the inland of the state of São Paulo with eight elderly individuals with Human Immunodeficiency Virus. The analysis was performed by means of content analysis, in the thematic modality. Results: four thematic categories emerged: Life context before the diagnosis; Way of infection, HIV suspicion and confirmation by the elderly; Living with HIV and Family/Social relations: among supports and preconceptions. Conclusion: the elderly individuals interviewed revealed the disease as a condition that exceeds their biological aspects, since it essentially involves the social, family and psychological contexts.